Headquarter resource allocation strategies and subsidiary competitive or cooperative behavior: Achieving a fit for value creation - Henrik Dellestrand; Philip Kappen; Olof Lindahl (Journal of Organization Design, 2020)
Integrating insights from the literature on the multinational corporation into current perspectives on resource allocation, we argue that the ability of headquarters to create value through resource allocation to subsidiaries within the multinational corporation is contingent on the complementary fit between the resource allocation strategy and the dominant behavior of the receivers of the resources. We expound on a theory and an explanation for the volatility of value creation generated by headquarter resource allocation that includes multiple layers of hierarchy. As a corollary, we extend and contribute to the theorizing on headquarters-subsidiary relations and resource allocation by illustrating different scenarios of the resource allocation process. More specifically, we develop a two-by-two matrix of the resource allocation process that corresponds to different resource allocation strategies of headquarters (winner-picking and cross-subsidization) and subsidiary behavior (collaboration or competition) in multinational corporations. We argue that, depending on which scenario within the matrix is brought to the fore, our understanding of how the resource allocation process plays out between headquarters and subsidiaries will differ and therefore influence value creation within the multinational corporation.
Keywords: 650; Headquarter value creation; Headquarters-subsidiary relations; Multinational corporations; Resource allocation; Winner-picking; Cross-subsidization; Competition; Collaboration